PENGARUH PERILAKU GURU DAN VARIASI MENGAJAR TERHADAP MOTIVASI SERTA DAMPAKNYA PADA HASIL BELAJAR SISWA DI KECAMATAN TALANG UBI - Fadri, Fadri (Jurnal Ilmu Manajemen, 2017)
The results of this study indicate that the behavior of teachers, the variationsin teaching and learning motivation of students simultaneously influence thestudents’ learning outcomes the students of state senior high school in thedistrict of Talang Ubi regency of Penukal Abab Lematang Ilir. For the effectof partially found that there are a positive and significant influence teachers’behavior partially on students’ learning outcomes, and there is a significantnegative influence of variations of teaching and students’ learning motivationpartially on students’ learning outcomes.